Durvalumab Plus Chemotherapy for Advanced Biliary Tract Cancer Treatment: Insights from the TOPAZ-1 Trial - Ralph Fritsch (healthbook TIMES. Oncology Hematology)
Biliary tract cancers (BTCs) are a difficult-to-treat group of tumors with an overall poor prognosis. Until 2022, combination chemotherapy was the first-line treatment standard for patients with advanced BTCs, achieving a moderate patient survival improvement. The evolution of chemoimmunotherapy has since shifted the first-line treatment landscape for advanced BTCs. In 2022, the publication of results from the pivotal phase III TOPAZ-1 trial marked a critical turning point, showing that adding durvalumab to standard chemotherapy with cisplatin and gemcitabine (CG) significantly improved overall survival in previously untreated patients with unresectable and metastatic BTCs. TOPAZ-1 marked the first major advancement in BTC treatment for more than a decade. This review summarizes the clinical evidence supporting the addition of durvalumab to CG in this indication, including the latest 3-year follow-up data from the TOPAZ-1 trial, presented at the Cholangiocarcinoma Foundation (CCF) 2024 Annual Conference and at the European Society for Medical Oncology Gastrointestinal Cancers (ESMO GI) Congress 2024, alongside real-world outcome data reflecting two years of clinical practice since FDA approval of durvalumab plus CG for first-line treatment of BTC. Additionally, we briefly touch on the underlying molecular mechanisms leading to synergy between immunotherapy and chemotherapy in BTC treatment and the potential implications for future BTC treatment strategies.